Pembelajaran Ekonomi Pada Masa Pandemi Covid-19 - Maskhur Dwi Saputra (Universitas Negeri Surabaya, 2022)
This study seeks to find out how economics teachers carry out online learning during the COVID-19 pandemic. This research method uses a qualitative descriptive type, while data collected using interviews with several economics teachers in the Surakarta senior high schools using WhatsApp. The data were collected using purposive and snowball sampling. The results showed that the economics teachers prepared learning instruments at the beginning of the semester. However, the instruments were only the edited instruments from the previous semester. The economics teachers only adjusted them. The instruments made were only as administrative requirements for reports to the local education office. The instruments were not implemented during the learning process. Economics teachers used several media to connect with their students such as WhatsApp Group, Google Classroom, Google Meet, and YouTube. For learning assessment, they used Google Form, Quizzzz, Quipper School, Mentimeter, Kahoot, and the school's e-learning software.